A review on the current available controlling methods of basal stem rot (BSR) disease in oil palm plantation: advantages and disadvantages of the methods / Sakinah Mohd Zabli - Zabli, Sakinah Mohd (Faculty of Plantation and Agrotechnology, 2016)
This review paper aims to discuss about the current available methods for controlling basal stem rot (BSR) disease with their advantages and disadvantages of each control method for BSR. BSR disease which caused by Ganoderma boninense sp. has been widely known as the threat disease in oil palm plantation that caused significant losses in oil palm industry. Thus, many controlling methods have been applied to manage and reduce the disease infection of the pathogen. Cultural, chemical, biological methods and other early detection technologies have been practiced and studied to cure this disease. However, to date there is no available methods yet to totally cure this disease because the symptoms only appear at late stage of the disease. Each of the available controlling methods has advantages to help in controlling the outbreak and infection of the disease. Nevertheless, there is a limitation in the control methods that should be considered before using the methods . This review paper consists of four main focused topics which are cultural, chemical , biological controls and other technologies that are available in controlling BSR disease.